Species of the genus Eurydema (Hemiptera: Heteroptera: Pentatomidae) in Far East Asia: An integrated approach using morphological, molecular, and data crossing analyses for taxonomy - Jung, Sunghoon; Kerzhner, Izyaslav M.; Lee, Seunghwan (Zootaxa, 2011)
In a revision of four previously described species of the genus Eurydema in Far East Asia, we confirm only two species, one of which consists of two subspecies: E. dominulus (Scopoli 1763) [= E. pulchra (Westwood 1837), syn. nov.], E. gebleri gebleri Kolenati 1846, and E. gebleri rugosa Motschulsky 1861 [stat. nov.]. In order to prove the above taxonomic changes, we focused on three major analyses; (1) morphological study (color patterns), (2) molecular identification (DNA barcording) and (3) cross–breeding (inter–specific copulation, fertilization). The results of these analyses were sufficient to confirm the new taxonomic changes. According to the cross–breeding analysis, interspecific copulation between males of E. dominulus (= E. pulchra) and females of E. g. gebleri or E. g. rugosa occurs in nature, but the eggs laid by the interspecific copulation were unfertilized. Two subspecies, E. g. rugosa and E. g. gebleri, preserve their own unique coloration patterns; this was confirmed by the results of intra–subspecific copulation and breeding. However, the 1 st progeny from the inter–subspecific copulation of E. g. rugosa♂ X E. g. gebleri♀ (or E. g. gebleri♂ X E. g. rugosa♀) were confirmed to have the coloration patterns inherited from E. g. gebleri.